El Excentrico, 1974-03-05 - Garcia, Humberto:::Publisher::::::::::::; Garcia, Bert:::Manager::::::::::::; Garcia, Marc:::Editor:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 5, 1974 [5 de marzo de 1974]. No volume of issue number. Cover has photographs of Lupe Badillo, Rachel Anne Garcia, Leticia Leanos, Adriana Rodriguez, and Yolanda Serrano from the San Jose G.I. Forum's 14th Annual Queen Pagent & Coronation Ball at the Santa Clara County Fairgrounds.